Biochar of Reed (Phragmites autralis) on Representative Locations in Mekong Delta of Vietnam - Dang, Ngoc Thi Hong; Thai, Luom Thanh; Danh, Mo; Ngo, Thien Van; Nguyen, Bao Manh Ngoc (Journal of Ecohumanism, 2025)
This experiment purpose is finding that using biochar of reed plants (Phragmites autralis); it is a plant species grows a seasonal cycle, it also is a very high biomass in Mekong Delta (MD) of Vietnam. To evaluate fresh, dry biomass and made of reed plants biochar to use them provide bio-organic fertilizer for rice plant (ST 25) in experiment. To achieve this aims some experiments have done by methods in laboratory of The Forestry Institute of Southern Vietnam are contents follow as:(1) investigating biomass of fresh, dry reed plants and made of biochar by use the local method; (2) analyses the chemical indicators in 3 different locations tis area on trunks, leaves, flowers in study area; (3) identify chemical indicators of peat land on 3 different locations of MD; (4) adsorption with pig urine and chemical fertilizer (nitrogen, phosphorus and potash) to see the retention off chemical components dispersed into the environment in the adsorbed biochar; (5) use the formulas of reed plant biochar mixed peat and mineral inorganic fertilizer. The results showed: The reeds in 3 locations of MD can provide big amount of biomass to make of reed biochar fertilizer; reed biochar can adopted as ammonium, nitrate, nitrogen, phosphorus and kalium the pig urine and it also adopted inorganic fertilizer as nitrogen, phosphorus and Kalium. Thus it is possible to use for application treatment environment in the region polluted and planting local rice ST 25 in the experiment area in MD. Biomass and biochar of reed in MD are big amount for the material of environment treatment and agriculture fertilizer; in chemical indicators of trunks, leaves and flowers in locations have some indictors are difference and some are not differences; the chemical indicators of some location are not differences; the mixed biochar, peat and inorganic in formulas in 5 days and 10 days were not differences; biochar can adsorb some chemical components of pig urine and nitrogen, phosphorus and kalium fertilizer; biochar can mixed peat and inorganic mineral fertilizer to planting rice ST 25 in Mekong Delta.